2016
DOI: 10.1016/j.semcdb.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Making muscle: Morphogenetic movements and molecular mechanisms of myogenesis in Xenopus laevis

Abstract: Xenopus laevis offers unprecedented access to the intricacies of muscle development. The large, robust embryos make it ideal for manipulations at both the tissue and molecular level. In particular, this model system facilitates the ability to fate map early muscle progenitors, visualize cell behaviors associated with somitogenesis, and examine the role of signaling pathways that underlie induction, specification, and differentiation of cells that comprise the musculature system. Several characteristics that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 152 publications
(168 reference statements)
0
11
0
Order By: Relevance
“…To determine whether the brain is required for the onset and/or patterning of myotomes, we evaluated the muscle phenotype at two relevant time points, corresponding to the different myogenic waves (reviewed in ref. 23 ): early- (stages 30–41; first and second waves completed) and late- (stages 42–48; third wave completed) stages after brain removal, respectively.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether the brain is required for the onset and/or patterning of myotomes, we evaluated the muscle phenotype at two relevant time points, corresponding to the different myogenic waves (reviewed in ref. 23 ): early- (stages 30–41; first and second waves completed) and late- (stages 42–48; third wave completed) stages after brain removal, respectively.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic temporal and spatial expression patterns of these factors orchestrate the main steps of muscle development: lineage specification of muscle cells, differentiation of myocytes, fusion into myofibers, and formation of muscle groups (reviewed in ref. 23 ). Future developments integrating in vivo physiological monitoring with transcriptional reporters will address the interaction of neurotransmitter and bioelectric signals from the brain with the transcriptional control of these and other important factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that P2X5 may be the major P2 receptor regulating somitogenesis. The easiness of Xenopus as an in vivo model for myogenesis makes this vertebrate embryo an ideal model to apprehend the functional roles of P2X5 during myogenesis (Sabillo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after formation, in response to inductive signals from adjacent tissue, somites differentiate into three compartments with different cell fates (myotome, dermatome, and sclerotome) (Brand-Saberi et al, 1996;Christ and Ordahl, 1995;Keynes and Stern, 1988). However, several studies have shown that compartmentalization begins before somite formation in the frog Xenopus laevis (Della Gaspera et al, 2012;Sabillo et al, 2016).…”
Section: Vertebral Development In Anuransmentioning
confidence: 99%